PERBANDINGAN KURIKULUM SEKOLAH DASAR INDONESIA DAN FILIPINA PADA KONTEKS PENDIDIKAN DASAR ASIA TENGGARA - Juliana Margareta Sumilat; Jini Carolina Dien (STKIP Subang, 2025)
This study aims to compare the elementary education curricula implemented in Indonesia and the Philippines, focusing on curriculum structure, learning approaches, educational goals, and core subjects taught at the primary school level. The background of this research is rooted in the importance of understanding the differences in educational systems within Southeast Asia to identify opportunities for collaboration and quality improvement through the exchange of best practices between countries. The study was conducted through a literature review and analysis of official documents from each country's Ministry of Education, along with secondary references from international organizations such as UNESCO and SEAMEO. The findings show that although both countries have a six-year duration for elementary education, there are fundamental differences in their curriculum approaches, where Indonesia currently implements the Merdeka Curriculum emphasizing the Pancasila student profile and differentiated instruction, while the Philippines adopts the K to 12 Curriculum focusing on core competencies and 21st-century skills development. The Indonesian curriculum tends to emphasize contextual learning and local wisdom, whereas the Philippine curriculum integrates an outcome-based education approach with standardized national benchmarks. The conclusion of this study suggests that both countries possess unique strengths and challenges, and mutual learning from each other's curriculum policies could serve as a strategic step in enhancing the quality of elementary education across Southeast Asia.